The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s10750-008-9603-x
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of deep open drains on water quality and biodiversity of receiving waterways in the Wheatbelt of Western Australia

Abstract: On each occasion, water quality parameters were measured and the macroinvertebrate fauna was sampled. Significant differences in water quality and macro-invertebrates were observed between the untreated sites and those affected by the drain discharge. Surface water at untreated sites was always fresh (<3 ppt), alkaline (pH 7.6-8.9) and turbid (49-600 NTU), whereas treatment sites were always saline (28-147 ppt), acidic (pH 1.9-3.8) and mostly clear (0-100 NTU).No recovery of water quality was observed with dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Many studies have found freshwater invertebrate species richness to decrease with an increase in salinity (Cale et al 2004, Waterkeyn et al 2008, Stewart et al 2009). Pinder et al (2005) identified 4.1 g TDS/L as the threshold above which species richness declined in isolated wetlands in the Australian wheatbelt.…”
Section: àmentioning
confidence: 99%
“…Many studies have found freshwater invertebrate species richness to decrease with an increase in salinity (Cale et al 2004, Waterkeyn et al 2008, Stewart et al 2009). Pinder et al (2005) identified 4.1 g TDS/L as the threshold above which species richness declined in isolated wetlands in the Australian wheatbelt.…”
Section: àmentioning
confidence: 99%
“…Stewart et al. (2008) found that no recovery had occurred up to 20 km downstream of a deep drainage complex discharging saline, acidic ground water into a natural watercourse.…”
Section: Which Models Best Conceptualise Ecological Change In Shallowmentioning
confidence: 99%
“…Ground waters in the eastern wheatbelt are generally strongly acidic (pH <3.5) and typically very saline (6000–8000 mS m −1 ). As a consequence, deep drains in this region, which often discharge to streams or wetlands, contain high levels of iron, aluminium, cobalt, copper, zinc and lead, and during periods of low flow, exhibit extreme acidity (pH < 3) and salinity (10 000–20 000 mS m −1 ) (Stewart, Strehlow & Davis, 2008).…”
Section: What Stressors Occur In Southwestern Australia?mentioning
confidence: 99%
“…The intent is to drain low-lying land, using a network of deep drains and bunding (an artificial embankment that prevents water entering a wetland, diverting it to a drain). However, these drains often intercept acid sulphate soils, leading to acidification of nearby wetlands, as has occurred elsewhere in the Wheatbelt (Stewart et al 2009).…”
Section: Management Of Wetlandsmentioning
confidence: 99%